(untitled) (Педагогіка вищої та середньої школи, 2006)
The article substantiates psychological-pedagogical conditions of adaptation period of first-year students to teaching and educational process at the establishment of higher education. The author submits for consideration and shows the essence of the adaptation process, reveals the factors conditioning difficulties of successful adaptation for first-year students to the system of higher education, gives recommendations of organizing work with first-year students aiming at the overcoming of psychological barrier in the "teacher-student" system.